Prevalence of pesticides in Krško-Brežice polje aquifer - Mali, Nina; Koroša, Anja; Urbanc, Janko (Geologija, 2021)
Groundwater pollution with pesticides is a problem that occurs all over the world as well as in Slovenia. Considering the past high loads of groundwater with pesticides, the purpose of the presented research was to determine the presence of pesticides in the groundwater of Krško-Brežiško polje in the period 2018-2019 and to check the applicability of the passive sampling method. A total of 21 groundwater samples were taken at 11 locations and 2 samples each in the Sava and Krka rivers. We identified 15 pesticides and their degradation products. Atrazine and its degradation product desethylatrazine were most frequently determined in groundwater samples. They are followed by desethylterbutylazine, terbutylazine, metolachlor and simazine. Atrazine, desethylatrazine, chlortoluron, metolachlor and terbuthylazine were detected in surface water. A total of 24 samples were taken in groundwater and surface water using the qualitative passive sampling method. We singled out 8 pesticides that appear in two campaigns. The frequency and occurrence of individual pesticides by both methods are comparable. Passive sampling has proven to be an appropriate method of identifying the presence of pesticides. The highest loads in the Krško-Brežiško field arise from the agricultural land areas. Groundwater is more contaminated with pesticides in the central part of the field in the direction of groundwater flow from west to east. In the groundwater of the Krško-Brežice field, atrazine and desethylatrazine are still the most frequently detected pesticides with higher concentrations, despite a 20 years long ban on the use of atrazine-based plant protection products.